Cycling intellectualization in Smart Cities - Makarova, I. V.; Boyko, A. D.; Shubenkova, K. A. (EAI Endorsed Transactions on Smart Cities, 2017)
Intellectualization is the basis for managing Smart Cities. This involves infrastructure development and design of vehicles equipped with intelligent modules, which provide the control ability. Along with it, the transition to “green”, safe and sustainable modes of transport, such as bicycle, should be realized. The widespread use of environmentally friendly bicycles is constrained by a number of reasons. The first is the absence of models designed for physically untrained people and the second is that almost half of all deaths on the world’s roads are among pedestrians and cyclists. We propose to solve these problems in two ways: development of an information system for bicycle infrastructure planning and modelling and creating control system of Smart Bike with adaptive electric drive that turns on when it’s necessary. Functional requirements for the proposed control system, its algorithm and the conceptual scheme of interaction between system’s modules are presented in the article.